Use of multi-gene panels in patients at high risk of hereditary digestive cancer: position statement of AEG, SEOM, AEGH and IMPaCT-GENÓMICA consortium - Carballal, Sabela; Balaguer, Francesc; Bujanda, Luis; Capellá, Gabriel; González Santiago, Santiago; Jover, Rodrigo; Moreira, Leticia; Pineda, Marta; Ruiz-Ponte, Clara; Sánchez Heras, Ana Beatriz; Serrano Blanch, Raquel; Soto, José Luis; et al. (Gastroenterología y hepatología, 2024)
This position statement, sponsored by the Asociación Española de Gastroenterología, the Sociedad Española de Oncología Médica, the Asociación Española de Genética Humana and the IMPaCT-Genómica Consortium aims to establish recommendations for use of multi-gene panel testing in patients at high risk of hereditary gastrointestinal and pancreatic cancer. To rate the quality of the evidence and the levels of recommendation, we used the methodology based on the GRADE system (Grading of Recommendations Assessment, Development and Evaluation). We reached a consensus among experts using a Delphi method. The document includes recommendations on clinical scenarios where multi-gene panel testing is recommended in colorectal cancer, polyposis syndromes, gastric and pancreatic cancer, as well as the genes to be considered in each clinical scenario. Recommendations on the evaluation of mosaicisms, counseling strategies in the absence of an index subject and, finally, constitutional analysis after identification of pathogenic tumor variants are also made.